Coastal Economic Transformation in Malang through Fintech Innovation: Digital Strategies for Fishermen’s Community Independence and Food Security - Durratun Nashihah; Firnanda Al-Islama Achyunda Putra; Anandhayu Mahatma Ratri; Saskia Dicha Prisilia; Risa Lidia Putri Wijayani (Alesha Media Digital, 2025)
The transformation of financial technology (fintech) innovation in strengthening economic independence and food security among coastal communities in Malang Regency. The research employed a qualitative descriptive method with a participatory approach (PAR) through stages of socialization, training, implementation of the Saku Laut application, mentoring, and evaluation. The results show that fintech improves transaction efficiency, financial literacy, and digital market access. Most fishermen have used Saku Laut for financial recording and product marketing. Collaboration among academics, village governments, and local communities is key to realizing an inclusive and sustainable transformation of coastal economies.